The possible role of ant larvae in the defence against social parasites. Issue 1898 (13th March 2019) - Pulliainen, Unni; Helanterä, Heikki; Sundström, Liselotte; Schultner, Eva
Abstract : Temporary social parasite ant queens initiate new colonies by entering colonies of host species, where they begin laying eggs. As the resident queen can be killed during this process, host colonies may lose their entire future reproductive output. Selection thus favours the evolution of defence mechanisms, before and after parasite intrusion. Most studies on social parasites focus on host worker discrimination of parasite queens and their offspring. However, ant larvae can also influence brood composition by consuming eggs. This raises the question whether host larvae can aid in preventing colony takeover by consuming eggs laid by parasite queens. To test whether larvae could play a role in anti-parasite defence, we compared the rates at which larvae of a common host species, Formica fusca, consumed eggs laid by social parasite, non-parasite, nest-mate, or conspecific non-nest-mate queens. Larvae consumed social parasite eggs more than eggs laid by a heterospecific non-parasite queen, irrespective of the chemical distance between the egg cuticular profiles. Also, larvae consumed eggs laid by conspecific non-nest-mate queens more than those laid by nest-mate queens. Our study suggests that larvae may act as players in colony defence against social parasitism, and that social parasitism is a key factor shaping discrimination behaviour in ants.